MAHYUDDIN DT. SUTAN MAHARAJA SEBAGAI PENGGERAK EKONOMI PEREMPUAN DI MINANGKABAU AWAL ABAD KE-20 - Addi Arrahman (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Mahyudin Dt. Sutan Maharaja in Sulit Air is better known as a journalist and traditional leader. In fact, Mahyudin Dt. Sutan Maharaja, through her journalistic activities, has been the driving force for women's economy in Minangkabau in the early 20th century. This is evidenced by his efforts to establish Kerajinan Minangkabau Laras Nan Dua (1907), Women's Weaving School (1909), Vereeniging Pemadjukan Kepandaian Bertenoen (1914) and Sarikat Sekolah Tenun (1914). He was also directly involved in the creation of the Kerajinan Andeh Setia (1912), which later inspired the founding of Kakak Saijo (1913) and Andeh Sakato (1913). Through this economic movement in the weaving sector, Dt. Sutan Maharaja drives the women's economy in Minangkabau.